Methylation of multiple genes in hepatitis C virus associated hepatocellular carcinoma - Zekri, Abdel-Rahman N. (J Adv Res, 2014)
We studied promoter methylation (PM) of 11 genes in Peripheral Blood Lymphocytes (PBLs) and tissues of hepatitis C virus (HCV) associated hepatocellular carcinoma (HCC) and chronic hepatitis (CH) Egyptian patients. The present study included 31 HCC with their ANT, 38 CH and 13 normal hepatic tissue (NHT) samples. In all groups, PM of APC, FHIT, p15, p73, p14, p16, DAPK1, CDH1, RARβ, RASSF1A, O(6)MGMT was assessed by methylation-specific PCR (MSP). APC and O6-MGMT protein expression was assessed by immunohistochemistry (IHC) in the studied HCC and CH (20 samples each) as well as in a different HCC and CH set for confirmation of MSP results. PM was associated with progression from CH to HCC. Most genes showed high methylation frequency (MF) and the methylation index (MI) increased with disease progression. MF of p14, p73, RASSF1A, CDH1 and O(6)MGMT was significantly higher in HCC and their ANT. MF of APC was higher in CH. We reported high concordance between MF in HCC and their ANT, MF in PBL and CH tissues as well as between PM and protein expression of APC and O(6)MGMT. A panel of 4 genes (APC, p73, p14, O(6)MGMT) classifies the cases independently into HCC and CH with high accuracy (89.9%), sensitivity (83.9%) and specificity (94.7%). HCV infection may contribute to hepatocarcinogenesis through enhancing PM of multiple genes. PM of APC occurs early in the cascade while PM of p14, p73, RASSF1A, RARB, CDH1 and O(6)MGMT are late changes. A panel of APC, p73, p14, O6-MGMT could be used in monitoring CH patients for early detection of HCC. Also, we found that, the methylation status is not significantly affected by whether the tissue was from the liver or PBL, indicating the possibility of use PBL as indicator to genetic profile instead of liver tissue regardless the stage of disease.